Thirty years after “interferon-β2: interleukin-6 at the host-tumor interface - Sehgal, Pravin B. (Contemporary Oncology/Współczesna Onkologia, 2010)
My laboratory stumbled on to “interferon-2” (IFN-2) in 1980 and subsequently cloned and assigned the human gene to chromosome 7. By 1988 this cytokine, also independently discovered by several other investigators, was dubbed “interleukin-6” (IL-6). Already in 1988-1989 we discovered that IL-6 was an almost invariant presence at the host-tumor interface in a variety of human solid tumors with both the tumor cells and stromal elements showing strong-to-moderate IL-6 immunoreactivity. The early studies also showed that circulating IL-6 was commonly increased in cancer patients and that glucocorticoids and estradiol-17 inhibited the IL-6 promoter. Today, the contributions of IL-6/STAT3 signaling have emerged as central to the interplay between infection and cancer, in promoting cancer metastases (e.g. breast, colon, liver) and in explaining gender- and obesity-related bias in cancer incidence (e.g. of liver cancer – less in women compared to males but high in obesity). Moreover, the well-known aging-related increase in cancer incidence is also now increasingly explained in terms of a “senescent secretory phenotype” which includes the increased production of IL-6 by tumor, stromal and infiltrating cells. Indeed, our early data (1991-1993) showing that cancer-derived mutants of p53 upregulated the IL-6 promoter, in contrast to wild-type (wt) p53 and wt Rb which inhibited, already pointed to a mechanism for dysregulated autocrine production of IL-6 by cancer cells – a mechanism that has since been extended by others. Additionally, it was shown already in 1989-1994 by Tamm and colleagues that IL-6 affected the “social” behavior of breast cancer cells – increased motility, cell-cell and cell-substrate dyshesion and epithelial-to-mesenchymal transformation. That these effects underlie the ability of paracrine or autocrine IL-6 to enhance the invasiveness and metastasis ability of tumor cells is now evident in animal models. In addition to the “canonical”, i.e. transcriptional functions of IL-6-activated STAT3, recent observations on the IL-6-induced targeting of activated Tyr-phosphorylated STAT3 to cytoplasmic sequestering endosomes and the involvement of non-Tyr-phosphorylated STAT3 in regulating microtubule dynamics, Ras-mediated cell transformation and tumorigenicity, and mitochondrial respiration highlight novel “non-canonical” functions of STAT3 in the cytoplasm of cancer cells.